USE OF THE HAWALA SYSTEM IN IMPLEMENTING INFORMAL INTERNATIONAL MONEY TRANSFERS - FRADYNSKYI, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the evolution and institutional basis of the system of international money payments "hawala", which was formed in the Islamic world. Similar payment systems exist in Asian countries (India, Thailand, Philippines).The existence of such a system is determined by the functioning of informal international channels for making monetary payments. Analysis of the functional principles of this system allows us to assert that it is a highly effective, extremely reliable and stable scheme for international transactions. It is a financial institution that was created outside the official legal field. Hawala can be considered as informal oral agreements that are based on complete trust and are able to ensure the fulfillment of the terms of the agreement by its participants, without relying on compliance with existing requirements of international or national legislation.The main advantages of using hawala in practice are summarized, which include the existence of a wide network of intermediaries; complete confidentiality for participants in the transaction of funds; the existence of absolute trust of all its participants; operation in the "24 hours, 7 days a week" mode, a minimum of bureaucratic procedures, a fairly low level of commission for the service provided. It is concluded that its existence is ensured by the needs of migrant workers to make money transfers from the country where they are received to the country where their families live under the conditions of confidentiality, speed, reliability and a small fee for the service. Despite the fact that hawala is used by representatives of the criminal world, it is not worth talking about its illegal nature, because it mainly serves the monetary turnover of funds that were received within the official economy and from which taxes were paid in their country of origin.
Keywords: migrant workers; income; money; remittances; hawala; hawaladar; shadow economy